Comparative anatomical and histological features of the kidney in Harrier (Circus aueroginosus), Chicken (Gallus domesticus) and Mallard duck (Anas platyrhynchos: Dhyaa, Ab.Abood; Ali, F. Reshag; Azhar, S. K. and Myson, A. Ahmed - Abood, Dhyaa Ab. (The Iraqi Journal of Veterinary Medicine, 2014)
The aim of this study was to compare anatomical and histological of the kidney in three type of birds. The study revealed that, in harrier species the cranial lobe of kidney was the largest with elongated shape. In mallard the cranial lobe was small round-oval, while middle and caudal lobe were lobulated and larger .In chicken the caudal lobe was the largest. Statistically, in harrier the mean length of cranial lobe (20±0.1mm) and the width of the middle lobe (5±0.5mm) were significantly higher than those of mallard (10±0.3mm) (8.0.2mm) and chicken (15±0.2mm) (4±0.4mm) respectively. The mean weight of the kidney in harrier is (5.8±0.20g) this value significantly was higher than those of mallared (8.9±0.11g) and chicken (6.8±0.10g) in compare to the total body weight. Histologically, in harrier species the kidney had larger cortical region and the nephron types were numerous of mammalian type in medulla and few of reptilian type was presented in sub-capsular region. In mallard species the renal lobule was relatively divided into two equal cortical and medullary regions and the nephrons showed two types, numerous of mammalian and reptilian types presented in medulla and intermediate zone of kidney. In chickens the cortical region was the larger compared to medullary region which contained numerous mammalian types and few of reptilian type.